Biocompatible Colloidal Suspensions Based on Magnetic Iron Oxide Nanoparticles: Synthesis, Characterization and Toxicological Profile - Coricovac, Dorina-Elena; Moacă, Elena-Alina; Pinzaru, Iulia; Cîtu, Cosmin; Soica, Codruta; Mihali, Ciprian-Valentin; Păcurariu, Cornelia; Tutelyan, Victor A.; Tsatsakis, Aristidis; Dehelean, Cristina-Adriana (Frontiers in Pharmacology, 2017)
The use of magnetic iron oxide nanoparticles in biomedicine has evolved intensely in the recent years due to the multiple applications of these nanomaterials, mainly in domains like cancer. The aim of the present study was: (i) to develop biocompatible colloidal suspensions based on magnetic iron oxide nanoparticles as future theranostic tools for skin pathology and (ii) to test their effects in vitro on human keratinocytes (HaCat cells) and in vivo by employing an animal model of acute dermal toxicity. Biocompatible colloidal suspensions were obtained by coating the magnetic iron oxide nanoparticles resulted during the solution combustion synthesis with a double layer of oleic acid, as innovative procedure in increasing bioavailability. The colloidal suspensions were characterized in terms of dynamic light scattering (DLS) and transmission electron microscopy (TEM). The in vitro effects of these suspensions were tested by means of Alamar blue assay and the noxious effects at skin level were measured using non-invasive methods. The in vitro results indicated a lack of toxicity on normal human cells induced by the iron oxide nanoparticles colloidal suspensions after an exposure of 24h to different concentrations (5, 10 and 25 µg·mL-1). The dermal acute toxicity test showed that the topical applications of the colloidal suspensions on female and male SKH-1 hairless mice were not associated with significant changes in the quality of barrier skin function.